Social Value of Public Information: Comment: Morris and Shin (2002) Is Actually Pro-Transparency, Not Con - Svensson, Lars E. O (American Economic Review, 2006)
Social Value of Public Information: Comment: Morris and Shin (2002) Is Actually Pro-Transparency, Not Con by Lars E. O. Svensson. Published in volume 96, issue 1, pages 448-452 of American Economic Review, March 2006